Adverse Effects of Hydroalcoholic Extracts and the Major Components in the Stems of Impatiens balsamina L. on Caenorhabditis elegans. (23rd February 2017) - Jiang, Hong-Fang; Zhuang, Zi-Heng; Hou, Bei-Wei; Shi, Bao-Jun; Shu, Cheng-Jie; Chen, Lei; Shi, Guo-Xin; Zhang, Wei-Ming
Abstract : Impatiens balsamina L. (Balsaminaceae), an annual herb found throughout China, has been extensively used in traditional Chinese medicine (TCM). However, our knowledge regarding the adverse effects of I. balsamina in vivo is very limited. In this present study, the nematode Caenorhabditis elegans model was employed to fully assess the adverse effects of hydroalcoholic (EtOH 55%) extracts of I. balsamina stems (HAEIBS) in vivo. After exposure to 10 mg/mL HAEIBS, the major organism-level endpoints of C . elegans of percent survival, frequency of head thrash and body bends, and reproduction had decreased by 24%, 30%, and 25%, respectively. The lifespan of C. elegans was also greatly reduced after HAEIBS exposure compared to the controls . The active compounds in HAEIBS were separated using high speed countercurrent chromatograph (HSCCC) and characterized by high performance liquid chromatography (HPLC) and nuclear magnetic resonance (NMR). Two compounds, lawsone and 2-methoxy-1, 4-naphthoquinone (MNQ), and their adverse effects were then more thoroughly detailed in this study. It was found that lawsone is the major toxin in HAEIBS with a higher toxicity than MNQ in terms of negative impact on C. elegans mortality, locomotion, reproduction, and lifespan. Our data also suggests that the C. elegans model may be useful for assessing the possible toxicity of other Chinese medicines, plant extracts, and/or compounds.